Perceived Training Needs of Farmers about Dairy Farming in Karnataka : A Perspective of Farmers and Veterinarians - B.L. Balaraju , Mahesh Chander, Prakash Khandekar, Prakashkumar Rathod, (Indian Journal of Extension Education, 2022)
..